MASALAH PENARIKAN KEMBALI TANAH WAKAF OLEH AHLI WARIS DARI WAKIF - Sulviana Livita Agustina Maulida (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe Wakif who has paid his land even though the wakaf land has not been certified is already considered lawful. And the land represented shall be a clean and free land of any encumbrance or dispute, because to ensure the certainty of legal rights and certainty. Because wakaf is a legal act of a person or legal entity that separates a portion of his or her possessions, in the form of property land and institutionalizes it forever for the sake of worship or other public purposes in accordance with the teachings of Islam.For wakaf land that has not been certified and registered in the deed of pledge of waqf in the Office of Religious Affairs, so for the wakaf land can not be withdrawn by his heirs for any reason. Because this is a wakif legal act to escape from the right of ownership, where wakif memakafkan his property with the aim of amalah religious life in accordance with the teachings of Islam and Government Regulation No. 28 of 1977. Thus for land wakaf that has not been certified to ensure the existence Certainty of rights and legal certainty for the wakaf land, must be made a certificate of awqaf in the Land Office. So that there is no problem or dispute about the wakaf land recall by heirs of wakif.In the practice of land ownership in the event of a dispute, the majority of the people in the Samarinda Municipality do not wish to bring the dispute to the Court. But first settled by way of deliberation between the disputing parties in each village or village witnessed in the presence of Village Head or Village Head. And if an agreement is reached, a peace statement will be made by the local urban village office to prove that the wakaf land is clearly represented. Except where the parties to the dispute can no longer be reconciled in a kinship, the case may be continued to be brought to the Religious Courts, especially the Religious Courts of Samarinda Municipality.